Is Corporate R&D Investment in High-tech Sectors more Efficient? Some Guidelines for European Research Policy - Raquel Ortega-Argilés; Maria-Cristina Piva; Lesley Potters; Marco Vivarelli (European Commission, Joint Research Centre (JRC), 2009)
This paper discusses the link between R&D and productivity across the European industrial and service sectors. The empirical analysis is based on both the European sectoral OECD data over the period 1987-2002 and on a unique micro longitudinal database consisting of 532 top European R&D investors over the six-year period 2000-2005. The main conclusions are as follows. First, the R&D stock has a significant positive impact on labour productivity; this general result is largely consistent with previous literature in terms of the sign, the significance and the magnitude of the estimated coefficients. More interestingly – both at sectoral and firm levels - the R&D coefficient increases monotonically (both in significance and magnitude) when we move from the low-tech to the medium and high-tech sectors. This outcome means that corporate R&D investment is more effective in the high-tech sectors and this may need to be taken into account when designing policy instruments (subsidies, fiscal incentives, etc.) in support of private R&D. However, R&D investment is not the sole source of productivity gains; technological change embodied in gross investment is of comparable importance on aggregate and it is the main determinant of the productivity increase in the low-tech sectors. Hence, an economic policy aiming to increase productivity in the low-tech sectors should support the overall capital formation.
Keywords: O33; 330; R&D; productivity; high-tech sectors; innovation and industrial policy